2016
DOI: 10.1016/j.addbeh.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence expectancies and quit attempts

Abstract: Introduction Several scales have been developed to measure expectancies about smoking cessation. This secondary analysis tested the reliability and validity of one of the most commonly used expectancy measures - the Perceived Risks and Benefits of Quitting Scale (PRBQ). Methods Smokers (n = 143) who planned to quit at some point in the next 3 months entered an observational study in which they called an Interactive Voice Response system nightly for 3 months to report quit attempts and abstinence. They comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Few studies to date have assessed the PRBQ's ability to predict quit attempts and/or abstinence. Hughes and Naud (2016) found that while the PRBQ demonstrated excellent internal and retest reliability and modest concurrent validity with related measures, there was no significant relationship between PRBQ scores and quit attempts or abstinence. Since this particular study only involved smokers who endorsed the intention to quit smoking within three months, further research would be helpful to assess predictive validity of this measure among a wider variety of smokers.…”
Section: Abstinence Outcome Expectanciesmentioning
confidence: 87%
“…Few studies to date have assessed the PRBQ's ability to predict quit attempts and/or abstinence. Hughes and Naud (2016) found that while the PRBQ demonstrated excellent internal and retest reliability and modest concurrent validity with related measures, there was no significant relationship between PRBQ scores and quit attempts or abstinence. Since this particular study only involved smokers who endorsed the intention to quit smoking within three months, further research would be helpful to assess predictive validity of this measure among a wider variety of smokers.…”
Section: Abstinence Outcome Expectanciesmentioning
confidence: 87%